2020
DOI: 10.15517/rbt.v69i1.42021
|View full text |Cite
|
Sign up to set email alerts
|

Traditional practices of the ethnoveterinary plants in the Kaghan Valley, Western Himalayas-Pakistan

Abstract: Introduction: Indigenous people in a far-flung mountainous area without basic facilities, mainly rely on medicinal plants to cope with various veterinary health problems. Objective: The present study was carried out to explore the traditional knowledge of ethnoveterinary practices in Kaghan Valley, district Mansehra, Western Himalayas-Pakistan. Method: Ethnoveterinary data were collected between February to October 2014 from nine villages of the Kaghan Valley by involving 80 local people include traditional he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…In contrast, the root decoction of B. lycium was previously reported to treat jaundice in cows, goats, and buffaloes from the Doda district of J&K (Khateeb et al 2015). The bark of B. lycium was also used to treat foot and mouth disease of cattle in Western Himalaya (Shoaib et al 2020). The present study reported the use of rhizomes of Bistorta amplexicaulis as a galactagogue.…”
Section: Comparison Of Traditional Uses With Previous Studiesmentioning
confidence: 67%
“…In contrast, the root decoction of B. lycium was previously reported to treat jaundice in cows, goats, and buffaloes from the Doda district of J&K (Khateeb et al 2015). The bark of B. lycium was also used to treat foot and mouth disease of cattle in Western Himalaya (Shoaib et al 2020). The present study reported the use of rhizomes of Bistorta amplexicaulis as a galactagogue.…”
Section: Comparison Of Traditional Uses With Previous Studiesmentioning
confidence: 67%
“…Due to these characteristics the territory is also a famous tourist attraction. Presently, these Districts are experiencing escalating human population, increase in tourism infrastructure, developmental projects (roads, dams), efforts of the China Pakistan Economic Corridor (CPEC) and high outmigration trends [ 5 , 6 ]. Consequently, rapid geo-physical changes can be seen, leading to the displacement of human population, high land-use for construction, destruction of agricultural lands and vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the root decoction of B. lycium is previously reported to treat jaundice in Cow, Goats, and Buffalo from the Doda district of J&K [44]. The bark of B. lycium is also used to treat mouth and foot disease of cattle in Western Himalaya [53]. The present study reported the use of rhizome of Bistorta amplexicaulis as a galactagogue.…”
Section: Comparative Assessment Of Traditional Uses With the Previousmentioning
confidence: 65%